Religious values and consumer behavior - Aglozo, Eric Y.; Cohen, Adam B. (Journal of Consumer Psychology, 2025)
Abstract Religion plays an important role in the lives of many individuals across the world, influencing various aspects of their lives. One area where the impact of religion is observed—but underexplored—is in consumer behavior. Research on the role of religion in consumer behavior is still developing, and we propose that focusing on religious values offers a promising direction for advancing this area of research. In this paper, we review existing research on values associated with religion and their influence on a wide range of consumer behavior, using Schwartz's values theory and the moral foundations theory as frameworks. But we also seek to build on these frameworks, and we conclude by suggesting potential avenues for future research on relationships between religious values and consumer behavior.